2012
DOI: 10.1371/journal.pone.0039499
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of Spontaneous Ca2+ Oscillation Causes Cell Death in Intraerythrocitic Plasmodium falciparum

Abstract: Malaria remains one of the world’s most important infectious diseases and is responsible for enormous mortality and morbidity. Resistance to antimalarial drugs is a challenging problem in malaria control. Clinical malaria is associated with the proliferation and development of Plasmodium parasites in human erythrocytes. Especially, the development into the mature forms (trophozoite and schizont) of Plasmodium falciparum (P. falciparum) causes severe malaria symptoms due to a distinctive property, sequestration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 54 publications
4
24
0
5
Order By: Relevance
“…6C shows an example of a spontaneous Ca 2+ response occurring before the IP 3 -dependent Ca 2+ release elicited by IP 3 uncaging. Spontaneous Ca 2+ transients have also been reported in other protists (18,32,33). Because spontaneous Ca 2+ transients were observed at similar rates in both uninduced and TbIP 3 R RNAi-induced cells (Fig.…”
Section: +supporting
confidence: 76%
“…6C shows an example of a spontaneous Ca 2+ response occurring before the IP 3 -dependent Ca 2+ release elicited by IP 3 uncaging. Spontaneous Ca 2+ transients have also been reported in other protists (18,32,33). Because spontaneous Ca 2+ transients were observed at similar rates in both uninduced and TbIP 3 R RNAi-induced cells (Fig.…”
Section: +supporting
confidence: 76%
“…This could confound our objective of identifying compounds that disrupt the DV. Nevertheless, Ca 2ϩ dysfunction would still be detrimental to parasite development, as blocking of Ca 2ϩ oscillations has been shown to be lethal to the parasite (29,30). Despite this, we believe that DCB does indeed destabilize the DV membrane, as postscreening validation showed that DCB induces phenotypes reminiscent of PCD ( Fig.…”
Section: Discussionmentioning
confidence: 93%
“…We recently, for the first time, demonstrated spontaneous Ca 2ϩ oscillation in Plasmodium falciparum. Furthermore, we showed that the blockage of this oscillation in the trophozoite stage by 2-aminoethyl diphenylborinate (2-APB) inhibited 1,4,5-trisphosphate (IP 3 )-induced Ca 2ϩ release (10)(11)(12), resulting in the death of the parasite (13). Chloroquine (CQ) is thought to exert its toxic effect in the intraerythrocytic parasite at the digestive vacuole (14).…”
mentioning
confidence: 99%